Ethnicity versus national language: a study in Malaysian universities setting - Mohd Tohar, Siti Nor Azhani; Ab Halim, Adlina; Mat Yacob, Siti Nor Baya (USIM Press, 2024)
The national language is an assimilation instrument for fostering racial unity in a multi-ethnic society. Nonetheless, ethnocentrism always plays a crucial role in upholding the national language across ethnic groups in Malaysia. A study in Malaysian higher education institutions (HEI) was conducted on 407 undergraduate students from Universiti Malaya (UM), Universiti Putra Malaysia (UPM), Universiti Selangor (UNISEL), and Multimedia University (MMU) using stratified random sampling to determine the differences in upholding the national language based on ethnic groups through three key dimensions, namely, i) fluency in speaking in the national language, ii) recognition of the importance of the national language, and iii) sophistication in the use of the national language. The results showed that there were significant differences in the upholding of the national language among the various ethnic groups. It was found that the Chinese students do not uphold the national language as much as the Malay and Indian students. This indicates that ethnicity plays a major role in determining the future of upholding the national language as the language of Malaysia. As Malaysian citizenship, ethnocentrism toward language should be managed to ensure assimilation of a multi-ethnic society through the most important medium, the Malay language as the national language of Malaysia.